Mechanistic insights into CO2-enhanced in-situ pyrolysis of tar-rich coal: Experiments and ReaxFF molecular dynamics simulations - Wei Guo; Panxi Yang; Zunyi Yu; Hongqiang Li; Keming Fu; Xuanzhi Hao; Yuxing Zheng; Zihao Tao; Jing Wang; Bolun Yang; Zhiqiang Wu (Fuel, 2026)

Fasudil attenuates fluoride-induced neuronal synaptic damage by inhibiting microglial inflammation - Wenjing Yang; Keming Bu; Xiaohan Ren; Shaoxiao Qin; Sheng Wang; Fang Chu; Chunqing Lu; Zhipeng Liu; Jiaying Liu; Yuqi Zhang; Xiyue Yang; Yanhui Gao; et al. (Environmental Toxicology and Pharmacology, 2026)

Predictive design of entrained-flow coal pyrolysis with cross-scale framework for high-value and low-carbon operation - Panxi Yang; Zunyi Yu; Keming Fu; Yuxing Zheng; Wei Guo; Zibo Huang; Hongqiang Li; Bolun Yang; Wenjing Zhou; Zhiqiang Wu (Chemical Engineering Journal, 2026)

Roxithromycin disrupts nitrogen uptake and stress responses in wheat under nitrogen deficiency - Binbin Yu; Yier Yang; Keming Yang; Chunyu Jiang; Zefeng Yang; Yiru Zhao; Xiaoli Wang; Beibei Shen; Shaohu Ouyang; Zhongzhi Chen (Plant and Soil, 2026)

Correlation analysis of heavy metal, antibiotics accumulation, and antibiotic resistance genes induced by long-term biogas slurry application - Binbin Yu; Chunyu Jiang; Keming Yang; Yang Zhang; Yang Gao; Zhongzhi Chen; Xiaoqing Qian; Shaohu Ouyang (Journal of Environmental Management, 2026)

Efficient elimination of highly lethal Vibrio parahaemolyticus in shrimp aquaculture by a vibriophage - Mingrui Li; Huaijin Jiang; Keming Shi; Haoyu Huang; Xiaojun Wang; Fang Li; Ke Pan; Yunlan Yang; Rui Zhang (Fish & Shellfish Immunology, 2026)

Numerical study on three-dimensional coupling characteristics for electromagnetism and flow in flat linear induction pump - Heyao Li; Zhuqian Zhang; Lixin Yang; Keming Bi; Xin Yan; Haojie Zhang; Xiao Chen (Annals of Nuclear Energy, 2026)

Distinct ecophysiological characteristics of two genetically similar vibriophages - Wenqing Li; Runqi Zhu; Keming Shi; Huiyu Ding; Shiying Ren; Song Xu; Jing Zhao; Nianzhi Jiao; Yunlan Yang; Rui Zhang (Marine Life Science & Technology, 2026)

A broad-spectrum vibriophage with potential for phage therapy against Vibrio alginolyticus in shrimp aquaculture - Keming Shi; Huiyu Ding; Wanxuan Zhong; Wenqing Li; Min Hsiao; Bu Xu; Haipeng Guo; Jing Zhao; Jie Xu; Demin Zhang; Yunlan Yang; Rui Zhang (Aquaculture, 2026)

Hematotoxicity of Fe- and Cr-based metal–organic framework nanoparticles in rockfish Sebastes schlegelii - Yiling Li; Junyu Ye; Meiyu Wang; Yang Gao; Bin Xia; Zhengguo Cui; Keming Qu (Marine Environmental Research, 2026)

Dual-beneficial synergistic Trichoderma-bacterial cross-kingdom SynCom facilitates Medicago sativa productivity and soil organic carbon sequestration in saline-alkaline soil - Weijie Liu; Rongrong Liu; Zhe Tang; Yu Zhang; Xinwei Deng; Keming Yang; Fengge Zhang (Plant and Soil, 2026)

A subsidence prediction model-driven InSAR phase unwrapping approach for large-gradient deformation in mining areas - Kegui Jiang; Keming Yang; Zijun Yang; Qiyong Zhang; Wenwen Li; Xinxin Zhang (Advances in Space Research, 2026)

Effects of PD-1 inhibitors on ovarian function-based on two-sample mendelian randomization and visualization experimental validation - Jiaxin Zheng; Na Zhu; Chang Liu; Xiang Li; Keming Zhang; Zhuo Yang; Danbo Wang; Bo Liu (Reproductive Toxicology, 2025)

Crop rotation mitigates soil fungal diversity loss under warming or increased moisture - Zhibo Zhou; Keming Yang; David Tissue; Zhong Wei; Le Li; Zhe Tang; Lukuan Fu; Hanqin Li; Tingting Sheng; Hongwei Liu; Yingjun Zhang; Fengge Zhang (Agriculture, Ecosystems & Environment, 2025)

A lytic vibriophage as a potential biocontrol agent against vibriosis in aquaculture - Yunlan Yang; Wanxuan Zhong; Huiyu Ding; Keming Shi; Haipeng Guo; Demin Zhang; Lanlan Cai; Min Hsiao; Jie Xu; Rui Zhang (Fish & Shellfish Immunology, 2025)

Lipid droplet-targeting fluorescent probes for monitoring hydrogen sulfide in ferroptosis - Chen Wang; Zhaomin Wang; Bingyan Li; Ziye Yang; Ruo Yang; Keming Zhu; Yong Liu (Analytica Chimica Acta, 2025)

The Application of Digital Twin Technology in the Development of Intelligent Aquaculture: Status and Opportunities - Jianlei Chen; Yong Xu; Hao Li; Xinguo Zhao; Yang Su; Chunhao Qi; Keming Qu; Zhengguo Cui (Fishes, 2025)
Aquaculture is vital for global food security but faces challenges like disease, water quality control, and resource optimization. Digital twin technology, a real-time virtual replica of physical aquaculture systems, emerges as a transformative solution. By integrating sensors and data analytics, it enables monitoring and optimization of water quality, feed efficiency, fish health, and operations. This review explores the current adoption status of digital twins in aquaculture, highlighting applications in real-time monitoring and system optimization. It addresses key implementation challenges, including data integration and scalability, and identifies emerging opportunities for advancing sustainable, intelligent aquaculture practices.

Numerical and experimental study of CO2 jet impingement on curved surfaces with different phases - Qian Chen; Laibin Zhang; Jianchun Fan; Yunpeng Yang; Keming Hu; Yang Fu (Process Safety and Environmental Protection, 2025)

Significance of temperature and salinity in the dynamics of diatoms and dinoflagellates along the coastal Yellow Sea - Chenshi Weng; Dongsheng Ding; Qian Yang; Lin Zhu; Jun Sun; Keming Qu; Zhengguo Cui; Yuqiu Wei (Progress in Oceanography, 2025)

Predatory protist promotes disease suppression against bacterial wilt through enriching plant beneficial microbes at the early stage of plant growth - Yuqi Song; Chen Liu; Keming Yang; Shiqi Sun; Lin Wang; Cansheng Yuan; Yangchun Xu; Wu Xiong; Qirong Shen; Zhong Wei (Plant and Soil, 2025)

Biological characteristics and genome analysis of Citrobacter freundii phage K1M - Keming Xie; Chang Liu; Guangfeng Liu; Peng Zhu; Zheng Yang; Lihong Yuan; Jingzhe Jiang (Archives of Virology, 2025)

Multisource remote sensing and ensemble learning for multidimensional monitoring of heavy metals on mine surfaces - Yanru Li; Keming Yang; Xinru Gu; Lishun Peng; Xinyang Chen (Environmental Geochemistry and Health, 2025)

Self-healing waterborne polyurethane originated from waste PET and their composites with polypyrrole for stretchable strain sensor - Keming Zhu; Lan Yang; Xing Zhou; Xuan Zhang; Yaya Hao; Fan Li; Wanqing Lei; Qi Wang; Guosheng Wang (Chemical Engineering Journal, 2025)

An artificial intelligence and blockchain technology-based data management framework for multicenter randomized controlled trials - Dongyuan Yun; Xiaohang Wu; Xi Chen; Yahan Yang; Yuanjun Shang; Shaopeng Liu; Dinesh Visva Gunasekeran; Duoru Lin; Lixue Liu; Lanqin Zhao; Wenben Chen; Jingjing Chen; et al. (Science Bulletin, 2025)

Implications of seawater characteristics on dissolved heavy metals in near-shore surface waters of the Yellow Sea - Minghao Li; Dongsheng Ding; Yong Xu; Qian Yang; Jun Sun; Keming Qu; Zhengguo Cui; Yuqiu Wei (Marine Pollution Bulletin, 2025)

Impacts of sedimentary characteristics and diagenesis on reservoir quality of the 4th member of the Upper Triassic Xujiahe formation in the western Sichuan basin, southwest China - Xianliang Chen; Youliang Ji; Keming Yang (Marine and Petroleum Geology, 2024)

Spatial-temporal pattern of ecosystem services and sustainable development in representative mountainous cities: A case study of Chengdu-Chongqing Urban Agglomeration - Liang Chen; Ying Yao; Keming Xiang; Xiaoai Dai; Wenyu Li; Hang Dai; Ke Lu; Weile Li; Heng Lu; Yang Zhang; Huan Huang; Meilian Wang (Journal of Environmental Management, 2024)

Meta-Analysis Study on the Role of Biochar on Soil Nitrogen Cycling - Binbin Yu; Keming Yang; Min Cui; Zilong Chen; Yuanyuan Dai; Xiaoqing Qian; Zhongzhi Chen (Journal of Soil Science and Plant Nutrition, 2024)

Extraction of vegetation disturbance range using aboveground biomass estimated from Sentinel-2 imagery in coal mining areas with high groundwater table - Kegui Jiang; Keming Yang; Xianglin Dong; Xinyang Chen; Lishun Peng; Xinru Gu (Environmental Science and Pollution Research, 2024)

Bioaccumulation of polycyclic aromatic hydrocarbons and their human health risks depend on the characteristics of microplastics in marine organisms of Sanggou Bay, China - Qi Sui; Xiaobin Yang; Xuemei Sun; Lin Zhu; Xinguo Zhao; Zhihua Feng; Bin Xia; Keming Qu (Journal of Hazardous Materials, 2024)

Environmental controls on the seasonal variations of diatoms and dinoflagellates in the Qingdao coastal region, the Yellow Sea - Qingxuan Wang; Qian Yang; Lin Zhu; Zhengguo Cui; Keming Qu; Yuqiu Wei (Marine Environmental Research, 2024)

Strength characteristics and carbonation depth evolution of modified magnesium slag based solid waste storage backfill materials - Zhiyu Fang; Lang Liu; Wei He; Keming Han; Hang Lan; Yuheng Gao; Weiji Sun; Zhen Han; Lei Xia; Pengyu Yang (Journal of Environmental Chemical Engineering, 2024)

Environmental forcing of phytoplankton carbon-to-diversity ratio and carbon-to-chlorophyll ratio: A case study in Jiaozhou Bay, the Yellow Sea - Yingzhe Wang; Zhengguo Cui; Dongsheng Ding; Qian Yang; Lin Zhu; Keming Qu; Jun Sun; Yuqiu Wei (Marine Pollution Bulletin, 2023)

Fine mapping and candidate gene analysis of qSB12YSB, a gene conferring major quantitative resistance to rice sheath blight - Yu Wang; Quanyi Sun; Jianhua Zhao; Taixuan Liu; Haibo Du; Wenfeng Shan; Keting Wu; Xiang Xue; Chao Yang; Jun Liu; Zongxiang Chen; Keming Hu; et al. (Theoretical and Applied Genetics, 2023)

Dual CNN cross-teaching semi-supervised segmentation network with multi-kernels and global contrastive loss in ACDC - Keming Li; Guangyuan Zhang; Kefeng Li; Jindi Li; Jiaqi Wang; Yumin Yang (Medical & Biological Engineering & Computing, 2023)

Amine-functionalized cotton for the treatment of oily wastewater - Yiling Ao; Ji'an He; Keming Chen; Mingzhao Zhu; Fan Ye; Liwei Shen; Ying Yang; Xuening Feng; Zejun Zhang; Yuqi Tang; Yuanzhu Mi (Environmental Research, 2023)

Research on the spatiotemporal prediction of mining deformation with subcritical extraction integrated with D-InSAR technology - Keming Yang; Zhixian Hou; Xiangping Wei; Wei Gao; Yanru Li; Xinming Ding; Shuang Wang; Yaxing Li; Hengqian Zhao (Advances in Space Research, 2023)

RIN enhances plant disease resistance via root exudate-mediated assembly of disease-suppressive rhizosphere microbiota - Keming Yang; Ruixin Fu; Haichao Feng; Gaofei Jiang; Omri Finkel; Tianyu Sun; Mingchun Liu; Baowen Huang; Shan Li; Xiaofang Wang; Tianjie Yang; Yikui Wang; et al. (Molecular Plant, 2023)

Dynamic prediction of displacement and deformation of any point on mining surface based on B-normal model - Xinming Ding; Keming Yang; Cheng Zhang; Shuang Wang; Zhixian Hou; Hengqian Zhao (Environmental Science and Pollution Research, 2023)

Scale transfer learning of hyperspectral prediction model of heavy metal content in maize: From laboratory to satellite - Yanru Li; Keming Yang; Hengqian Zhao (International Journal of Remote Sensing, 2023)

Hydrocarbons removal and microbial community succession in petroleum-contaminated soil under hydrogen peroxide treatment - Bing Yang; Mi Zhou; Yuan Meng; Keming Chen; Jie Xu; Xiangfu Huang; Yucheng Liu; Lingli Li; Lili Ma; Mingyan Chen (Environmental Science and Pollution Research, 2022)

Non-destructive study on identifying and monitoring of Cu-Pb pollution in corn based on near-infrared spectroscopy - Yanru Li; Keming Yang; Bing Wu; Jianhong Zhang; Qianqian Han; Wei Gao (Environmental Science and Pollution Research, 2022)

Prediction of Longwall Progressive Subsidence Basin Using the Gompertz Time Function - Jian Wang; Keming Yang; Xiangping Wei; Xiaoyu Shi; Shuyi Yao (Rock Mechanics and Rock Engineering, 2022)

Molecular Analysis Associated with Early Flowering Mutant in Brassica napus - Jiawang Mao; Yanhua Yang; Ningning Wang; Keming Zhu; Yulong Li; Zheng Wang; Xiaoli Tan (Journal of Plant Biology, 2021)

Environmental factors affecting regional differences and decadal variations in the buried flux of marine organic carbon in eastern shelf sea areas of China - Qian Yang; Keming Qu; Shu Yang; Yao Sun; Yan Zhang; Mingying Zhou (Acta Oceanologica Sinica, 2021)

The Monitoring of the Pollution Degree of Maize Under Copper Stress - Chao Zhang; Keming Yang; Kunpeng Rong; Feng Cheng; Yan Li (Journal of the Indian Society of Remote Sensing, 2020)

Spectral Characteristics and the Study of Pollution Degree of Maize Leaves Under Copper and Lead Stress - Chao Zhang; Keming Yang; Yan Li; Feng Cheng; Kunpeng Rong (Journal of the Indian Society of Remote Sensing, 2020)

Perspective on Etiology and Treatment of Bipolar Disorders in China: Clinical Implications and Future Directions - Zuowei Wang; Chen Jun; Keming Gao; Haichen Yang; Yiru Fang (Neuroscience Bulletin, 2019)

Coccolithophore responses to the Pacific Decadal Oscillation in the East China Sea region of the Northwest Pacific from ad 1901 to 2013 - Shu Yang; Mingli Yuan; Qian Yang; Jiansheng Huang; Mengran Sun; Jun Sun; Keming Qu; Yao Sun (Journal of Quaternary Science, 2019)
A high‐resolution study of coccolithophores in a sediment core from the East China Sea (ECS) region of the Northwest Pacific revealed that fluctuations in coccolithophore assemblages responded well to the Pacific Decadal Oscillation (PDO) during 1901–2013. Emiliania huxleyi and Gephyrocapsa oceanica were the most dominant species, accounting for more than 97% of all the ten detected species. The variation of the two dominant species showed a significant positive correlation, and they both increased during peak values of the PDO. Decreased stratification and increased nutrient supplementation from the bottom water induced by lower sea surface temperatures in the ECS, which were associated with high PDO values, were responsible for the dominant coccolithophore increase. Similarly, the increase of Calcidiscus leptoporus also corresponded to low‐temperature and high‐nutrient conditions associated with the cold phase in the ECS (positive phase of the PDO). The responses of decadal C. leptoporus variations to changes in cold and warm phases of the PDO in the Northwest and Northeast Pacific indicate that C. leptoporus preserved in sediment cores represents a potential indicator for reconstructing phase changes of the PDO during ancient times.

Study on Heavy Metal in Soil Based on Spectral Second-Order Differential Gabor Transform - Pingjie Fu; Keming Yang; Feisheng Feng (Journal of the Indian Society of Remote Sensing, 2019)

Sex difference in the association of body mass index and BDNF levels in Chinese patients with chronic schizophrenia - Fang Yang; Keming Wang; Xiangdong Du; Huiqiong Deng; Hanjing Emily Wu; Guangzhong Yin; Yuping Ning; Xingbing Huang; Antonio L. Teixeira; João de Quevedo; Jair C. Soares; Xiaosi Li; et al. (Psychopharmacology, 2019)

A novel approach to evaluate potential risk of organic enrichment in marine aquaculture farms: a case study in Sanggou Bay - Shu Yang; Qian Yang; Xianli Song; Sai Liu; Keming Qu; Yao Sun (Environmental Science and Pollution Research, 2018)

Intein-mediated Cre protein assembly for transgene excision in hybrid progeny of transgenic Arabidopsis - Jia Ge; Lijun Wang; Chen Yang; Lingyu Ran; Mengling Wen; Xianan Fu; Di Fan; Keming Luo (Plant Cell Reports, 2016)

Burial fluxes and sources of organic carbon in sediments of the central Yellow Sea mud area over the past 200 years - Shu Yang; Qian Yang; Sai Liu; Deling Cai; Keming Qu; Yao Sun (Acta Oceanologica Sinica, 2015)

Identification and characterization of a wood-associated NAC domain transcription factor PtoVNS11 from Populus tomentosa Carr. - Li Yang; Yisu Hou; Xin Zhao; Wanxiang Lu; Yongli Li; Fan Yang; Shaohu Tang; Keming Luo (Trees, 2015)

PtrWRKY73, a salicylic acid-inducible poplar WRKY transcription factor, is involved in disease resistance in Arabidopsis thaliana - Yanjiao Duan; Yuanzhong Jiang; Shenglong Ye; Abdul Karim; Zhengyi Ling; Yunqiu He; Siqi Yang; Keming Luo (Plant Cell Reports, 2015)

Evaluation of Upper Triassic T3x5 Source Rocks (Western Sichuan Depression, Sichuan Basin) and their Hydrocarbon Generation and Expulsion Characteristics: Implication for Tight-Sand Gas and Shale Gas Accumulation Potential Assessment - Yingchun Guo; Xiongqi Pang; Dongxia Chen; Keming Yang; Zhenxue Jiang; Xiaopeng Zhang; Fujie Jiang (Natural Resources Research, 2013)

Molecular cloning, expression and characterization of a novel vacuolar protein sorting 4 gene in silkworm, Bombyx mori - Hengchuan Xia; Chunxia Zhang; Fan Feng; Yi Yuan; Yang Zhou; Xiaoyong Liu; Keming Zhu; Qin Yao; Keping Chen (Molecular Biology Reports, 2012)

Effects of confined space and near vision stimulation on refractive status and vitreous chamber depth in adolescent rhesus monkeys - YunXia Leng; WeiZhong Lan; KeMing Yu; BingQian Liu; ZhiKuan Yang; Zheng Li; XingWu Zhong; ShaoChong Zhang; Jian Ge (Science China Life Sciences, 2010)

Testing a Dynamic Complex Hypothesis in the Analysis of Land Use Impact on Lake Water Quality - QingHai Guo; KeMing Ma; Liu Yang; Kate He (Water Resources Management, 2010)

Structural styles of Longmen Mountain thrust belt, SW China - Wenzheng Jin; Liangjie Tang; Guimei Wan; Keming Yang; Zhizhou Lü; Yixin Yu (Journal of Earth Science, 2010)

Overexpression of Citrus junos mitochondrial citrate synthase gene in Nicotiana benthamiana confers aluminum tolerance - Wei Deng; Keming Luo; Zhengguo Li; Yingwu Yang; Nan Hu; Yu Wu (Planta, 2009)

KIFC1 participates in acrosomal biogenesis, with discussion of its importance for the perforatorium in the Chinese mitten crab Eriocheir sinensis - Keming Yu; Lin Hou; Jun-Quan Zhu; Xue-Ping Ying; Wan-Xi Yang (Cell and Tissue Research, 2009)

Transfer zones within the Longmen Mountains thrust belt, SW China - Wenzheng Jin; Liangjie Tang; Keming Yang; Guimei Wan; Zhizhou Lü; Yixin Yu (Geosciences Journal, 2009)

In vitro regeneration and Agrobacterium-mediated genetic transformation of Euonymus alatus - Yongqin Chen; Litang Lu; Wei Deng; Xingyu Yang; Richard McAvoy; Degang Zhao; Yan Pei; Keming Luo; Hui Duan; William Smith; Chandra Thammina; Xuelian Zheng; et al. (Plant Cell Reports, 2006)